Sistem Layanan Pembuatan Kartu Tanda Anggota (KTA) Berbasis Online Di Perpustakaan Jebres Surakarta - Putri, Rizky Adinda; Hastomo, Mursid Dwi; Pantjarani, Ari (Politeknik Harapan Bangsa Surakarta, 2024)
ABSTRACTThe service system is a system in which a party acts to provide service assistance to visitors to get something they want and satisfy visitors according to their expectations. This service system is very important because with this system everything will become easier, faster and more efficient. The Jebres Library is a library that stands in the midst of a community engaged in education. The agency has problems in terms of making Membership Cards that still use paper or an offline written system. This of course can cause problems, including the risk of being exposed to water, the long process of searching for data, and the risk of losing membership cards. The purpose of this research is to create an online-based membership card making service system at the Jebres Surakarta Library. The author uses the System Development Live Cycle (SDLC) method in the system development process. The programming language used is PHP and uses the MySQL database. The system that the author designed can produce applications that make it easier for agencies to make library membership cards at the Jebres Surakarta Library and can be accessed via the web. By using this information system, leaders can immediately find out the data for making library member cards every day.Keywords: system services, libraries, SDLC, PHP, MySQL